2010
DOI: 10.1108/s0733-558x(2010)0000031003
|View full text |Cite
|
Sign up to set email alerts
|

Research on categories in the sociology of organizations

Abstract: The concept of a ''category'' and the social process of ''categorization'' occupy a crucial place in current theories of organizations. In this introductory chapter to Research in the Sociology of Organization's volume on Categories in Markets: Origins and Evolution, we review published work in various streams of research and find that studies of organizational forms and identities, institutional logics, collective action frames, and product conceptual systems have key commonalities and predictable differences. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 89 publications
(131 reference statements)
0
117
0
7
Order By: Relevance
“…Empirical progress on issues of spanning has been rapid (Hannan, 2010;Negro et al, 2010b). This is due partly to the proliferation of archives and websites that assign categorical memberships to objects and also provide audience reactions.…”
Section: A New Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical progress on issues of spanning has been rapid (Hannan, 2010;Negro et al, 2010b). This is due partly to the proliferation of archives and websites that assign categorical memberships to objects and also provide audience reactions.…”
Section: A New Approachmentioning
confidence: 99%
“…1 Category-spanning objects have patterns of feature values that fit more than one genre (or other social concept) and, sometimes, their producers claim membership in more than one genre at one time or over time in a sequence of affiliations. Sociological studies show that conceptual boundaries do prove consequential in diverse domains: combining genres generally generates some form of direct or indirect devaluation (for reviews, see Hannan (2010) and Negro et al (2010b)). …”
mentioning
confidence: 99%
“…Identity can play a central role in establishing organizational legitimacy (see Navis & Glynn, 2011), yet communicating a hybrid identity is particularly challenging. Research on social categorization has shown that organizations spanning multiple categories are less easily understood by audiences (Negro, Kocak, & Hsu, 2010). For example, Zuckerman (1999Zuckerman ( , 2000 finds that firms that do not fit into a given business category receive less attention from analysts, which affects their share price.…”
Section: Organizational Identitymentioning
confidence: 99%
“…In studies of markets, sociologists now conceptualize the dynamics of the interface of producers and audiences in these terms (Zuckerman, 1999). Work on institutional fields, organizational forms, product classification systems, and social movements have been enriched by attention to categorical dynamics (for reviews, see DiMaggio (1997); Benford and Snow (2000); Hannan (2010) ;Negro, Koçak, and Hsu (2010)). This line of work shows that category boundaries are construed and controlled by the perceptions of audience members and that category-based processes have significant impact on market outcomes.…”
Section: Discussionmentioning
confidence: 99%